DISSEMINATING OSTEOCONDRITE: CASE REPORT (CIPEEX, 2022)
OSTEOCHONDRITIS DISSECANS (OD) IS A PATHOLOGY CHARACTERIZED BY PARTIAL OR TOTAL DETACHMENT OF THE HYALINE CARTILAGE FRAGMENT FROM THE SUBCHONDRAL BONE, WHICH MAY OR MAY NOT DETACH AND REMAIN AS A FREE ARTICULAR BODY. THE CHOICE OF TREATMENT IS BASED ON THE CONSERVATIVE AND SURGICAL METHOD, WHICH IS INTENDED TO PRESERVE CARTILAGE, IF POSSIBLE, OR TO USE RESTORATIVE PROCEDURES, AND THE PURPOSE OF THIS WORK IS TO REPORT A TYPICAL CASE OF OSTEOCHONDRITIS DISSECANS. A 20-YEAR-OLD MALE PATIENT COMPLAINED OF PAIN FROM PROGRESSIVE ONSET TO SLIGHT EXERTION, EVEN IF LIGHT, SUCH AS WALKING FOR A LONG TIME OR JUMPING; FELT PAIN IN THE LEFT KNEE AND SWELLING, LIMITING MOVEMENTS OF THE LEFT LEG. AFTER A YEAR AND SIX MONTHS OF ONSET OF SYMPTOMS HE SOUGHT MEDICAL SERVICE, WITH THESE COMPLAINTS OF PAIN WELL LOCATED IN THE MIDDLE OF THE PATELLA. THE DOCTOR PERFORMED TESTS DURING THE PHYSICAL EXAMINATION, BUT NONE TESTED POSITIVE. THE PAIN DID NOT RADIATE, HAD INTENSITY 7/10 AND CONTINUED TO PERFORM MOVEMENTS. THE DOCTOR REQUESTED X-RAY AND HIS RESULT SUGGESTED A DIAGNOSIS OF OD, AFTER WHICH HE REQUESTED AN MRI OF THE LEFT KNEE, WHICH CONFIRMED THE DIAGNOSIS. A THERAPEUTIC PLAN WAS DRAWN FOR THE PATIENT, INDICATING A PHYSIOTHERAPEUTIC TREATMENT IN ADDITION TO THE USE OF ANALGESICS TO CONTROL PAIN. AT THE END OF 3 YEARS OF FOLLOW-UP, THERE WAS NO SPONTANEOUS RESOLUTION OF THE DISEASE AND THE ORTHOPEDIST OPTED FOR THE ARTHROSCOPIC FIXATION OF LEFT KNEE OD LESION (PLACEMENT OF 3 HEBERTS) IN POSTEROMEDIAL POSITION. AFTER 2 MONTHS, THE PATIENT IS UNDER PHYSIOTHERAPEUTIC TREATMENT, AND PAIN HAS BEEN CONTROLLED, BUT THERE IS STILL MOVEMENT LIMITATION. ALTHOUGH OD IS NOT VERY RECURRENT IN THE GENERAL POPULATION, IT WAS OBSERVED THAT IT IS A PATHOLOGY THAT PRESENTS A GOOD PROGNOSIS, EVEN IN SURGICAL CASES, BESIDES THAT, THE LIMITATIONS ARE ELIMINATED AFTER TREATMENT AND RESOLUTION OF THE DISEASE.
Keywords: Osteochondritis Dissecans. Prevention. Early diagnosis.